Does Beta-Alanine Supplementation Potentiate Muscle Performance Following 6 Weeks of Blood Flow Restriction or Traditional Resistance Training? - Pessôa, Kassiana De Araujo; Cholewa, Jason Michael; Sousa-Silva, Rayssa; Xia, Zhi; Zagatto, Alessandro M. [UNESP]; Lancha-Jr, Antonio Herbert; Lauver, Jakob D.; Rossi, Fabrício Eduardo [UNESP]; Zanchi, Nelo Eidy (My University, 2023)
We aimed to compare the effects of beta-alanine on Traditional Resistance Training (TRAD) or Blood Flow Restriction Training (BFR). Methods: 19 subjects were randomly allocated to a Placebo (n = 10) or beta-alanine (n = 9) group. Subjects from both groups were trained unilaterally (unilateral arm curl) for six weeks, and each arm was trained using a different paradigm (BFR or TRAD). One repetition maximum (1RM) test measurements were performed before and after the strength training program. Work output was accessed as the total weight lifted (repetitions × weight lifted × sets) for the entire strength training program. Results: 1RM or total weight lifted was not increased by beta-alanine supplementation. However, the TRAD-trained arm showed a significantly increased 1RM and total weight lifted compared to the BFR arm (p < 0.05). Conclusion: We conclude that in the short-term (6 weeks) and following the current experimental conditions, beta-alanine does not benefit BFR or TRAD in terms of total weight lifted (volume of training) or maximal strength (1RM).
Keywords: performance; pre-workout; Resistance training